2008
DOI: 10.1177/152692480801800111
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transplant Education for Recipients to Increase Pursuit of Living Donation

Abstract: Recipients spent 10 median hours learning about transplant, primarily by speaking to medical staff (2-3 hours) and reading transplant brochures (0-1 hour). Twelve percent had not received any education before coming to the transplant center. At least 75% wanted education discussing the evaluation, surgery, and medical tests required of recipients and donors, as well as common transplant-related fears. Recipients who received living donor transplants were more interested in information about donors' evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…If not supplied with these skills, patients eligible for kidney transplant may prefer to wait for volunteers to approach them than to ask anyone directly. 16,45 …”
Section: Discussionmentioning
confidence: 99%
“…If not supplied with these skills, patients eligible for kidney transplant may prefer to wait for volunteers to approach them than to ask anyone directly. 16,45 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 Participants’ engagement in transplant learning activities was assessed by self-report. Participants reported the type of educational activity and the time spent on each activity.…”
Section: Methodsmentioning
confidence: 99%
“…Given that LDKT is the best treatment for most patients with ESRD, it seems appropriate to increase time spent on LDKT education, to begin education earlier in the disease process (e.g., delivered by general nephrologists and dialysis providers), and to re-discuss LDKT at various time-points (e.g., CKD diagnosis, dialysis initiation, transplant evaluation, while on waiting list). [9] Different combinations of LDKT educational content, amount of time spent, and delivery approaches have been evaluated with transplant candidates. [10–12] These trials have demonstrated techniques that result in improved knowledge of and more positive attitudes about LDKT, successful completion of transplant evaluation, increased LKD evaluations, and/or higher LDKT rates.…”
Section: Transplant Candidate Ldkt Educational Processesmentioning
confidence: 99%